The stoicism goes to the frontiers: the relations between Romans and Barbarians in Seneca’s thought (1st Century AD) - Jerce da Costa Junior, Cesar Luiz (Romanitas - Revista de Estudos Grecolatinos, 2025)
This article examines the rhetorical and argumentative construction of the so-called “barbarian” peoples in the philosophical thought of Lucius Annaeus Seneca (4 BC–65 AD). It also considers how the author understood the complex intercultural relationships that arose on the borders of the Roman Empire, especially those of the Rhine and Danube rivers, inhabited by Germanic and Sarmatian peoples. References to non-Romans are frequent in his writings, though not presented in a systematic way. Therefore, in order to obtain a broader picture of the subject, it is necessary to consider them collectively. Based on these discursive fragments, we aim to understand how Seneca perceived the world beyond the traditional Roman limes of his time, and to what extent barbarian peoples could serve as the foundation for ethical notions consistent with the Stoicism he embraced.